Interactions between CD44 and Hyaluronan in Leukocyte Trafficking - McDonald, Braedon; Kubes, Paul (Frontiers in Immunology, 2015)
Recruitment of leukocytes from the bloodstream to inflamed tissues requires a carefully regulated cascade of binding interactions between adhesion molecules on leukocytes and endothelial cells. Adhesive interactions between CD44 and hyaluronan have been implicated in the regulation of immune cell trafficking within various tissues. In this review, the biology of CD44-hyaluronan interactions in cell trafficking is summarized, with special attention to neutrophil recruitment within the liver microcirculation. We describe the molecular mechanisms that regulate adhesion between neutrophil CD44 and endothelial hyaluronan, including recent evidence implicating serum-derived hyaluronan associated protein (SHAP) as an important co-factor in the binding of hyaluronan to CD44 under flow conditions. CD44-hyaluronan mediated neutrophil recruitment has been shown to contribute to innate immune responses to invading microbes, as well as to the pathogenesis of many inflammatory diseases, including various liver pathologies. As a result, blockade of neutrophil recruitment by targeting CD44-HA interactions has proven beneficial as an anti-inflammatory treatment strategy in a number of animal models of inflammatory diseases.